Laboratory Assessments For Conventional And Fiber Reinforced Asphalt Mixtures To Enhance Pavement Performance - Jamil, Nurainin Hafizah (Universiti Sains Malaysia, 2021)
Nowadays, a high-quality and reliable asphalt pavement is desirable and become an important aspect of the highway asphalt pavement performance. A higherquality pavement can make regular rides safer and more comfortable. Asphalt binder modification and reinforced asphalt mixes are among the innovations to improve asphalt pavement performance. In this research study, asphalt mixture that was reinforced with Super Fiber Mix (SFM) was chosen as an alternative for asphalt pavement improvement. In the past five decades, the use of fibers was investigated and implemented in asphalt mixtures to improve pavement performance worldwide. The primary goal of this study was to examine the effect of additional fiber on laboratory performance and to compare the modified asphalt to conventional asphalt. The report outlines the features and properties of modified asphalt (SFM) blended with polypropylene and aramid fibers. The laboratory assessments for five major tests were conducted and those tests are the Marshall Stability and Flow test, Indirect Tensile Strength test, Resilient Modulus test, Dynamic Creep Modulus test, and the rutting test. Based on the results, the Marshall's stability values of the reinforced asphalt sample improved as much as 17.8% as compared to the conventional mixture. The flow values for both conventional and modified samples are within the allowable range. However, the flow value for the modified sample is lower (3.1 mm) as compared to 3.5 mm of the conventional asphalt, which implies that the modified asphalt mixture was stiffer. The SFM contains aramid fiber, which has high tensile strength and is proven through the increased indirect tensile strength results as well. The SFM also help to increase the Resilient Modulus value by approximately 24%. The dynamic creep test showed that the use of the SFM improved the modulus values and passed the minimum requirement. Meanwhile, the rut depths for both control and modified samples conform to the minimum requirement of 12 mm for rut depth by the PWD specification. In this case, the asphalt mixture enforced with the SFM exhibits similar performance with the conventional asphalt mixture. Overall, the asphalt mixture reinforced with the SFM exhibits better engineering properties as compared to the conventional asphalt mixture.